Comparing the reasons for suicide from attempt survivors and their families in Ghana - Asare-Doku, W.; Osafo, J.; Akotia, C.S. (BMC Public Health, 2019)
Background Family members are key in detecting early suicide warning signs. This study compared the reasons for suicidality as reported by attempt survivors with their family folks in Ghana. Methods A qualitative design was used to select a sample size of 20 (10 family members and 10 suicide attempt survivors). Thematic analysis was used to analyse the data. Results Analysis of the data showed two major themes: 1) Similar Reasons (where both families and attempt survivors consistently reported similar reasons for suicidality and 2) Different Reasons (where there were sharp divergences). Conclusions Findings from this study help to understand the readiness of attempt survivor family members to intervene early during suicidal crisis.
Keywords: Suicide; Attempt survivors; Families; Ghana